Replacement Value of Bambaranut Voandzeia subterranea Sievate for Soyabean Meal Glycin max on the Performance of Finisher Broiler Chicken - Ekenyem, B.U.; Onyeagoro, C.P. (International Journal of Poultry Science, 2006)
One hundred and sixty 4-week old broiler chicks were used in a 28-day feeding trial in a completely randomized design, to evaluate the performance of finisher broiler chicks fed varying replacement values of Bambaranut sievate (BNS) Voandzeia subterranea for soyabean meal (SBM) Glycin max. The four dietary treatments were further replicated four times. Treatments having 0%, 5%, 10% and 15% BNS replaced corresponding weights of SBM in the diets. Feed and potable water were supplied ad libitum while vaccination and medication were appropriately applied. The initial weight, final weight, weight gain, feed intake, feed conversion ratio, feed cost per kg gain were measured. Results show that birds on 0% and 5% BNS with weights 1.85kg and 1.83kg respectively were significantly (P< 0.05) heavier than those on 10% and 15% BNS weighing 1.68kg and 1.65kg respectively. This trend was also observed for weight gain where birds on 0% and 5% BNS were superior (P< 0.05) to those on 10% and 15% levels respectively. However, the initial weight and feed intake were not statistically different (P>0.05), feed conversion ratio and feed cost/kg gain were significantly (P< 0.05) different between their various treatment means. BNS was found to appreciably reduce cost of broiler chick production and could be included up to 15% in chicks diets.